A case of ROS1‐rearranged lung adenocarcinoma exhibiting pleural effusion caused by crizotinib. Issue 7 (20th May 2020) - Tachi, Hiroaki; Nishino, Kengo; Nakaizumi, Taisuke; Kuramoto, Kenya; Shimizu, Kei; Yamamoto, Yusuke; Kobayashi, Keisuke; Ichimura, Hideo; Sakata, Akiko; Nawa, Takeshi
Abstract : Reports of crizotinib‐induced pleural effusion in non‐small cell lung cancer (NSCLC) are limited. A 35‐year‐old Japanese woman was diagnosed with ROS1‐rearranged lung adenocarcinoma (primary left lower lobe, cT4N3M1c). Crizotinib was administered as first‐line therapy, and the primary and mediastinal hilar lymph node metastases rapidly shrank. On the fourth day of treatment, chest X‐ray demonstrated contralateral pleural effusion. On the 41st day of treatment, crizotinib was discontinued because of grade 3 neutropenia. Examination including surgical thoracoscopy did not reveal causative findings, and the continued cessation of drug administration enabled the right pleural effusion to decrease gradually and disappear, suggesting that this event was a side effect of crizotinib. The disease did not progress even though the drug was withdrawn for more than one year. In conclusion, crizotinib was considered to cause pleural effusion as an adverse event in a case of ROS1‐rearranged lung adenocarcinoma with a complete response.